DAMPAK KEBERADAAN PERKEBUNAN SAWIT KALTIM LESTARI TERHADAP PENDAPATAN MASYARAKAT DESA SABINTULUNG KECAMATAN MUARA KAMAN - Mahmud Syamsuddin; Wartomo; Elisa Herawati (JURNAL AGRIMENT, 2020)
With the existence of the oil palm company PT. Sawit Kaltim Lestari is intended to create jobs, expand job opportunities and business opportunities. Based on this, the oil palm company has a strategic meaning, which is expected to increase community income, support the balance of the economic structure and create and expand employment. Based on the explanation above, the problem in this study is how the impact of the establishment of the oil palm company PT. Sawit Kaltim Lestari towards community income in Sabintulung Village, Muara Kaman District. Then this study aims to determine the impact of the establishment of the oil palm company PT. Sawit Kaltim Lestari on community income in Sabintulung Village, Muara Kaman District